The earl and the pharaoh : from the real Downton Abbey to the discovery of Tutankhamun - Carnarvon, Fiona, Countess of (Harper, an imprint of HarperCollinsPublishers, 2022)
"Bestselling author the Countess of Carnarvon tells the thrilling behind-the-scenes story of the discovery of the tomb of Tutankhamun on its centennial, and explores the unparalleled life of family ancestor George Herbert--the famed Egyptologist, world-traveler, and 5th Earl of Carnarvon behind it--whose country house, Highclere Castle, is the setting of the beloved series Downton Abbey. Drawing on Highclere Castle's archives, the Countess of Carnarvon pays homage to her ancestor on the 100th anniversary of this extraordinary event. In vivid and dramatic detail, she brings into focus the larger-than-life characters and lustrous settings--as well as those twists of luck and tragedies that shaped Herbert's life. Across the early 1900s, Highclere saw no less drama than the fictional Downton Abbey, with early tragedies for the Earl and love affairs, as well highs of exorbitant wealth and trials of punishing debt. But above all there was adventure. While Herbert first went to Egypt for his health, this mysterious, romantic land would become a second home; the beloved place where he funneled his attentions over a period of decades, never quite realizing how great the fruits of his labors would prove"--